Efeito do uso de plásticos reciclados e óleo de cozinha sobre a qualidade do coque - Alison Frederico Medeiros Ferreira (2012)
The consumption and disposal of used plastic in Brazil have increased significantly over recent years, with a significant contribution to the composition of the municipal solid waste- MSW of about 10.9%, which represents a generation of 6.6 million tonnes per year of plastics. Currently, the main existing forms of recycling in Brazil cannot absorb all the plastic generated because of its degree of impurity. The other solid waste studied, was the used vegetable oil. Disposed in an inappropriate way it can cause serious environmental damage, such as clogging of pipes, efficiency reduction of treatment systems, among other problems. Thus, this study aims to evaluate the technical feasibility of the energetic recycling of plastic and used vegetable oil in coking ovens. It was prepared a typical composition of the existing MSW plastics, consisting of 33% HDPE, LDPE 5%, 10% PP, PET 21%, 24.8% PS, PVC 5.2%, 1% of cellulose and 0.5% of used vegetable oil. The wastes were added to the coal mixtures in a proportion of 1%, 2% and 3% of plastics and 0.5% of vegetable oil in order to evaluate the interference of these materials onthe coke quality. There were two types of experiments. The first was made in a hearth heating furnace- FSA with temperatures up to 900 °C and 7 hours. The second assay was performed in test box, which consists in put the mixtures of coal and plastic in cans of 18 L inside the pilot cokeoven for about 20 hours at a temperature of 1050-1 100 °C. The parameters of coke quality CSR, CRI, Ash, Volatile Matter and Sulfur were evaluated to identify the influence of the plastic and the used vegetable oil in the quality of coke. The results of CSR in the FSA showed a mean of 52.3% and 54.9% for the test box assays. The results of CRI varied in a range from 26.6% to 35.79 %. Considering the differences betweenthe experiments made and the industrial furnace, it can be concluded that the results obtained are consistent for the tests carried confirming the possibility of using plastic in the steelmaking process.